Exploring authentic food in Kelantan using mobile application / Muhamad Syafiq Aqim Sazeli - Sazeli, Muhamad Syafiq Aqim (2017)
Make “Simply Kelatelicious” is a mobile application that has been developed to assist user in finding restaurants that serve authentic food in Kelantan and as a medium for restaurant owner to promote their restaurant. Kelantan is famous with the variety of food and because of that Tourism and Culture Ministry in Kelantan launched a campaign to make Kelantan as food tourism. Based on interview and survey that has been made, there are several problems faced by people in finding authentic food in Kelantan such as do not know what authentic food available at Kelantan, do not know location of the restaurant that serve authentic food in Kelantan and no specific platform to promote authentic food and restaurants. This project is carried out with an aim to develop an Exploring Authentic Food in Kelantan using mobile application using the methodology Mobile Application Development Lifecycle (MADLC) that consist six (6) phases which are identification, design, development, prototyping, testing and maintenance. However, only three (3) phases are used in these projects to achieved objectives which are identification, design and development. Each phase contents several activities to be finished in order to achieve objectives. As a result, an application named Make “Simply Kelatelicious” is developed together with documentation of Software Requirements Specification (SRS) and Software Design Document (SDD). The challenges faced during running this project include skills and experience, lack of time, and understanding project plan. For the future work, the system needs to be improves in terms of features and areas cover since this system only covering Kelantan.